Breaking bad news: a cross-sectional study assessing SPIKES protocol adherence and other methods employed among medical doctors in Nigeria - Tope Michael Ipinnimo; Olumide Temitope Asake; Oluwafemi Oreoluwa Olowoselu; Taofeek Adedayo Sanni; Abolaji Paul Adekeye; Rasheed Adeyemi Adepoju; Gbenga Damilola Akinlua; Paul Oladapo Ajayi; Oluwole Michael Adeojo; Christiana Aderonke Afolayan; Tolulope Ayodeji Bamidele; Olaoye Michael Faleke; et al. (BMC Primary Care)
Abstract Background The SPIKES (Setting, Perception, Invitation, Knowledge, Empathy, and Strategy) protocol has been widely used in many developed countries for breaking bad news (BBN), however, serious uncertainty remains in its understanding and implementation in many developing nations. This study aims to assess adherence to SPIKES protocol and its associated factors, in addition to exploring alternative techniques used to BBN among medical doctors in Nigeria. Methods A cross-sectional study was conducted in Ekiti State, Nigeria among 245 medical doctors selected through a systematic sampling technique in May, 2024. A semi-structured questionnaire, adapted from a previous study was used to collect information on biodata, practice of SPIKES protocol, and an open-ended question that asked how the respondents break bad news. Frequencies, logistic regression, and content analysis (for the open-ended question) were conducted. Results Overall, 178 (72.7%) doctors fully adhered to the SPIKES protocol with Settings (98.4%), Perception (93.9%), Invitation (76.7%), Knowledge (99.2%), Empathy (98.0%) and Strategy (98.4%). Clinical position(p = 0.002) and education or training(p = 0.034) were significant on bivariate. Predictors of full SPIKES adherence were doctors at public tertiary (AOR = 0.132; 95%CI = 0.029–0.600) and public secondary/primary health facilities (AOR = 0.079; 95%CI = 0.012–0.502) than those in private health facilities; doctors that are pediatricians (AOR = 0.109; 95%CI = 0.023–0.515) than the general practitioners. Content analysis shows many doctors adopt the full SPIKES protocol, use different aspects of it (SPIKES variants viz the Knowledge and Empathy (KE), Setting and Knowledge (SK), and the Setting, Knowledge, and Empathy (SKE)), some use no specific protocol, adopt the religious/spiritual approach, and other (Blunt, Diplomatic and BATHE) methods/Approaches. Conclusions Achieving consistent BBN practice requires continuous training and more support as shown by variability in adherence influenced by factors such as training and education, healthcare facility, and specialty.